2019
DOI: 10.35940/ijrte.d5138.118419
|View full text |Cite
|
Sign up to set email alerts
|

Erosion and Sediment Control Best Management Practices in Agricultural Farms for Effective Reservoir Sedimentation Management at Cameron Highlands

N S M Noh*,
L M Sidek,
A Wayayok
et al.

Abstract: For many years, lands in Cameron Highland have been opened and leveled for agricultural farming and intensive crop production. Land-disturbing activities such as agricultural operations that are conducted on regions with steep slopes leads to a high potential of soil erosion, sedimentation and landslide occurrences. As a results, this phenomenon producing large amounts of sediment transported and deposited to the receiving waters or reservoirs. The development of best management practices (BMPs) for agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Table 1 shows the significant landslides occurrence in Cameron Highlands throughout the period spanning from 2016 to 2021. The annual precipitation in Cameron Highlands which is similar to other tropical mountainous areas recorded an average range of 2,500 to 3,000 millimetres per year [10]. The period of highest rainfall in Cameron Highlands occurs from March to May, as well as from November to December throughout the year.…”
Section: Landslide In Cameron Highlandsmentioning
confidence: 63%
“…Table 1 shows the significant landslides occurrence in Cameron Highlands throughout the period spanning from 2016 to 2021. The annual precipitation in Cameron Highlands which is similar to other tropical mountainous areas recorded an average range of 2,500 to 3,000 millimetres per year [10]. The period of highest rainfall in Cameron Highlands occurs from March to May, as well as from November to December throughout the year.…”
Section: Landslide In Cameron Highlandsmentioning
confidence: 63%
“…The recent study by [28] analyzed LULC changes in Kenya by using GIS and remote sensing techniques. Similarly, numerous studies have been reported to observe LULC changes in different catchments in Malaysia [29][30][31].…”
Section: Introductionmentioning
confidence: 92%
“…High levels of soil degradation and environmental contamination have resulted from the high use of fertilisers and pesticides by local farmers, followed by an increased frequency of major storm events (Wulandry et. al., 2018;Noh et al, 2019). Recent agricultural practices have led to significant soil erosion due to wind or flow, or both (Raj, 2002;Parveen & Kumar, 2012;Razali et al, 2018).…”
Section: Introductionmentioning
confidence: 99%